Adherence of obstructive sleep apnoea syndrome patients to positive airway pressure therapy - 10-year follow-up - Genzor, Samuel; Prasko, Jan; Vanek, Jakub; Asswad, Amjad Ghazal; Nadjarpour, Shayan; Sova, Milan (Biomedical papers, 2022)
Purpose. Continuous positive airway pressure (CPAP) is the most effective therapy for obstructive sleep apnoea syndrome (OSAS). Long-term adherence is necessary; however, it may be widely variable based on current literature, where the predicting factors are also not well defined. The aim of this study was to assess ten-year adherence to CPAP and to define factors influencing it. Methods. In total, 107 patients (91 males) were enrolled in this study, with an average age of 53.5 years (SD 10.1), with CPAP therapy being indicated (Apnoea-Hypopnoea Index - AHI > 15). Anthropometric and social status data have been obtained as well as the average use of CPAP through device memory. Results. Sufficient adherence (> 4 h per night) was found in 57% of patients in the first year with no subsequent significant change during the next 9 years. Adherence correlated significantly with the severity of OSAS - AHI (r = 0.321 over 5 years) and Epworth Sleepiness Scale (r = 0.317 over ten years) but did not correlate with the pressure used or the age of the patient. No statistically significant differences have been found between the sexes, the different mask groups, or the social status groups. Conclusion. Good adherence to CPAP therapy in OSAS patients is essential. According to our results, patients with more severe OSAS or more severe sleepiness seem to have better adherence.
Keywords: sleep apnoea syndrome; CPAP therapy; adherence to therapy; follow-up; social status